2010
DOI: 10.1073/pnas.1005909107
|View full text |Cite
|
Sign up to set email alerts
|

LuxR homolog-independent gene regulation by acyl-homoserine lactones in Pseudomonas aeruginosa

Abstract: Pseudomonas aeruginosa quorum control of gene expression involves three LuxR-type signal receptors LasR, RhlR, and QscR that respond to the LasI-and RhlI-generated acyl-homoserine lactone (acyl-HSL) signals 3OC12-HSL and C4-HSL. We found that a LasRRhlR-QscR triple mutant responds to acyl-HSLs by regulating at least 37 genes. LuxR homolog-independent activation of the representative genes antA and catB also occurs in the wild type. Expression of antA was influenced the most by C10-HSL and to a lesser extent by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…These delay the expression of quorum sensing-regulated genes, thereby reducing bacterial virulence both in vitro and in vivo (35,115). Recently, Chugani and Greenberg revealed an even higher level of complexity in P. aeruginosa AHL signaling, reporting a set of 37 genes whose expression was controlled by AHLs in the absence of LasR, RhlR, and QscR (34). These recent results raise questions about AHL quorum sensing regulation.…”
Section: Further Regulation Of the Ahl Systemsmentioning
confidence: 95%
“…These delay the expression of quorum sensing-regulated genes, thereby reducing bacterial virulence both in vitro and in vivo (35,115). Recently, Chugani and Greenberg revealed an even higher level of complexity in P. aeruginosa AHL signaling, reporting a set of 37 genes whose expression was controlled by AHLs in the absence of LasR, RhlR, and QscR (34). These recent results raise questions about AHL quorum sensing regulation.…”
Section: Further Regulation Of the Ahl Systemsmentioning
confidence: 95%
“…It is possible that the double-AI synthase mutant showed a more dramatic reduction in cas gene expression compared with the single mutants and the mutant lacking both receptor genes because of compensatory effects from the orphan QS receptor QscR, which promiscuously binds AIs (30). Another possibility is that the AIs regulate cas and csy expression through a pathway that operates independently of LasR, RhlR, and QscR, as has been discovered for a few genes in P. aeruginosa PAO1 (31).…”
Section: Significancementioning
confidence: 98%
“…It is possible that CHB regulation of gene expression is not mediated by a cognate receptor. Very recently, Chugani et al (5) found that acyl-homoserine lactone (acyl-HSL) regulation in P. aeruginosa does not follow the classical QS tenet in that it is not mediated by a LuxR-type transcription factor: even after disrupting all LuxR-type receptors, there were at least 37 genes that still responded to acyl-HSL.…”
Section: Discussionmentioning
confidence: 99%